Trajectory Tracking Control for a Spatial Parallel Manipulator Based on Differential- Algebraic Equations - Tran Xuan Minh, Nguyen Van Quyen, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The motion equations of parallel spatial manipulators are a system of complicated differential-algebraic equations. Sothe construction of enough accurate and relatively simple mechanical models is needed. This paper introduces two mechanical models which can be used by control for the 3-PRS parallel manipulator. Using the methods as PD control, PID control to control 3-PRS parallel manipulator based on two different mechanical models is the article's main content. The simulation results showed PD control method, PID showed good results when using enough accurate mechanical models.